STUDI AWAL SEBARAN BAHASA-BAHASA ETNIK DI PROVINSI BENGKULU - Ngudining Rahayu (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2018)
This preliminary study is intended to describe the distribution of languages of ethnic groups in Bengkulu Province. This research is based on geographic linguistics in the province of Bengkulu. The basic vocabulary instrument is 300 (Swadesh and Kern) and 150 cultural vocabularies. Data collection is carried out at a number of observed villlages proportionally. Data analysis was performed with lexicostatistics and dialectometry. The results show the following. With the exception of Enggano and the languages of ethnic immigrants, the Rejang, Lembak, Serawai, Pasemah, and Mukomuko languages are related to each other. The differences between these ethnic languages are mostly at the level of vowel sounds /a/, /o/ or /aw /, /é/ and /ê/, diphthong, nasal clusters such as /mp/, /nt/, /nc/, and /ngk/ on the one hand and /p/, /t/, /c/, /k/ on the other. Rejang language has 4 dialects, that are Lebong, Musi, Keban Agung and Pesisir. The distribution of Rejang ethnic languages covers Lebong District, part of Rejang Lebong, parts of Kepahiang, parts of Bengkulu Utara, and parts of Bengkulu Tengah Regency, while Mukomuko ethnic language distribution covers some areas of Mukomuko Regency. The spread of Lembak language covers Padang Ulak Tanding and Padang sub-districts in Rejang Lebong, and in some villages in Bengkulu and Bengkulu  Tengah Regency. Serawai language has distribution in  of Seluma and Bengkulu Selatan Regencies, in addition to some villages in Kepahiang Regency. Pasemah ethnic language has distribution in some areas of Kabupaten Kaur. The Lembak, Serawai, and Pasemah languages are used in the written tradition of the Ulu script. Some specimens of Ulu Lembak, Serawai, and Pasemah texts are preserved as family heirlooms or village heirlooms in the area of the ethnic language in question.Keywords: linguistics geography, ethnic language, Bengkulu